2012
DOI: 10.1172/jci57407
|View full text |Cite
|
Sign up to set email alerts
|

PTH-independent regulation of blood calcium concentration by the calcium-sensing receptor

Abstract: Tight regulation of calcium levels is required for many critical biological functions. The Ca 2+ -sensing receptor (CaSR) expressed by parathyroid cells controls blood calcium concentration by regulating parathyroid hormone (PTH) secretion. However, CaSR is also expressed in other organs, such as the kidney, but the importance of extraparathyroid CaSR in calcium metabolism remains unknown. Here, we investigated the role of extraparathyroid CaSR using thyroparathyroidectomized, PTH-supplemented rats. Chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 54 publications
(57 reference statements)
8
176
0
5
Order By: Relevance
“…Additional mechanisms, such as phosphorylation, palmitoylation, and trafficking, may also exist for claudin-14, -16, and -19 that explain more transient changes (within minutes) in paracellular Ca ++ transport during some in vitro recordings in perfused TALH tubules. 14,27 CaSR is the first identified G protein-coupled receptor to be activated by an extracellular ion-Ca ++ . 1 Its function has been shown to be crucial for many physiologic processes, including sperm generation, embryonic development, Ca ++ metabolism, neuronal excitability, etc., and underlie various diseases, such as hyper-and hypoparathyroidism, kidney stones, osteoporosis, Alzheimer disease, epilepsy, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional mechanisms, such as phosphorylation, palmitoylation, and trafficking, may also exist for claudin-14, -16, and -19 that explain more transient changes (within minutes) in paracellular Ca ++ transport during some in vitro recordings in perfused TALH tubules. 14,27 CaSR is the first identified G protein-coupled receptor to be activated by an extracellular ion-Ca ++ . 1 Its function has been shown to be crucial for many physiologic processes, including sperm generation, embryonic development, Ca ++ metabolism, neuronal excitability, etc., and underlie various diseases, such as hyper-and hypoparathyroidism, kidney stones, osteoporosis, Alzheimer disease, epilepsy, etc.…”
Section: Discussionmentioning
confidence: 99%
“…40 40 A direct support for the renal role of CaSR in defending hypercalcemia was provided by Toka et al 41 With a kidney-specific CaSR KO mouse model, Toka et al 41 have elegantly shown that the KO mice excrete significantly less Ca ++ in face of hypercalcemia, although their PTH secretion was intact. Loupy et al 14 have studied the renal role of CaSR in cases of hypercalcemia induced by the calcilytic compound NPS2143. In TPTX rats supplemented with a constant PTH level, NPS2143 administration elicited a significant decrease in urinary Ca ++ excretion without affecting net Ca ++ release from the bone or intestinal Ca ++ absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loupy et al showed that a CaSR antagonist increased Ca 2+ permeability in isolated perfused TALH, with no change in transepithelial voltage or Na flux. 80 This appears to be mediated by regulation of the expression of claudin-14. Activation of the CaSR causes robust upregulation of claudin-14, 81,82 which, through physical interaction, inhibits paracellular cation channels formed by claudin-16 and -19.…”
Section: Regulation Of Tal Claudins By Extracellular Calciummentioning
confidence: 99%
“…Both extracellular Ca 21 and PGE 2 activate the G i inhibitory G protein in TAL cells, opposing the stimulatory, G s -dependent effects of vasopressin on intracellular levels of cAMP (91). Extracellular Ca 21 exerts its effect through the CaSR, which is heavily expressed at the basolateral membrane of TAL cells (91,92); PGE 2 primarily signals through EP 3 PG receptors (76). The increases in intracellular Ca 21 due to the activation of the CaSR and other receptors directly inhibits cAMP generation by a Ca 21 -inhibitable adenylate cyclase that is expressed in the TAL, accompanied by an increase in phosphodiesterasedependent degradation of cAMP (91,93).…”
Section: Inhibitory Influencesmentioning
confidence: 99%